Rancang Bangun Visualisasi Panduan Fitness Berbasis Mobile (Studi Kasus: Atlas Sports Club Surabaya) - Arifiansyah, Riska Septian; Sutanto, Teguh; Purnama, Rangsang (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2012)
Weight-bearing exercise (fitness) has now become one of the urban lifestyle in the world, especially in Indonesia. The slogan "Healthy Life Begins with" being promoted by the Government appears to have been understood by the people of Indonesia. But not everyone can make fitness a healthy lifestyle due to the limitations of science and knowledge about the world of fitness itself. This has been anticipated by the provider of fitness gym, in this study conducted at the Atlas Sports Club Surabaya, namely by providing the Personal Trainer (PT), that is, those who assist customers in running fitness is good and right. But to be able to use the services provided by Personal Trainer where providers will cost more expensive than the cost to become a member (member). Based on the description, then be made based visualization applications mobile fitness guide that can help the member fitness Atlas Sportss Club Surabaya who do not use the services of Personal Trainer. This application guide contains a fitness movement that displayed visually through text and pictures and videos, nutritional guidance, control and alarm schedule a private workout scheduled gym classes at Atlas Sports Surabaya during the next month, and can provide information about the world of fitness the form of articles and tips that can be accessed easily and can be renewed. With this application the mobile phone can now be used as a medium of interaction, especially the visual guidance of mobile-based fitness guide. Keyword: Fitness, Personal Trainer, Visualisasi, Mobile Device.